RESCHEDULING RAILWAY TIMETABLES FROM AUTOMATED GUIDEWAY TRANSIT IN AIRPORT USING MAX PLUS â MODEL PREDICTIVE CONTROL METHODS - Hanif, Nadia
Rescheduling Railway timetable is one of the effort to minimize propagation delay time caused by the tardiness on departure time of railway. The tardiness of departure time without the increasment of speed to recover the delayed effect on the next cycle as a continuation act often leads to an accumulated number of passengers in stations. Furthermore, the economic losses and the company’s reputation are also the damaged factors due to the delay in departure time.On this thesis, the velocity is being modified to minimize the build-up in number of passengers. Modification of trains’ velocity based on the delay given is proven to reduce the delay propagation in departure time which is a nonlinear function with constraints. The timetable is modeled by Maxplus algebra. Based on railway timetable itself, the model then being optimized with quasi-Newton method as an approximation of Hessian matrix to get minimum delay time. This optimization method is combined with Model Predictive Control to get the number of cycles in which the timetable is already back to normal.